A-910823, a squalene-based emulsion adjuvant, induces T follicular helper cells and humoral immune responses via α-tocopherol component - Yoshioka, Yuya; Kobiyama, Kouji; Hayashi, Tomoya; Onishi, Motoyasu; Yanagida, Yosuke; Nakagawa, Takayuki; Hashimoto, Masayuki; Nishinaka, Anri; Hirose, Jun; Asaoka, Yoshiji; Tajiri, Minako; Hayata, Atsushi; et al. (Frontiers in Immunology, 2023)
Background: Adjuvants are chemical or biological materials that enhance the efficacy of vaccines. A-910823 is a squalene-based emulsion adjuvant used for S-268019-b, a novel vaccine against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that is currently in clinical development. Published evidence has demonstrated that A-910823 can enhance the induction of neutralizing antibodies against SARS-CoV-2 in humans and monkeys. However, the characteristics and mechanisms of the immune responses induced by A-910823 are not yet known. Methods and Results: To characterize A-910823, we compared the adaptive immune response profile enhanced by A-910823 with that of other adjuvants (AddaVax, QS-21, aluminum salt-based adjuvants, and empty lipid nanoparticle [eLNP]) in a murine model. Compared with other adjuvants, A-910823 enhanced robust humoral immune responses following potent T follicular helper (Tfh) and germinal center B (GCB) cell induction, without inducing a strong systemic inflammatory cytokine response. Furthermore, S-268019-b containing A-910823 adjuvant produced similar results even when given as a booster dose following primary administration of a lipid nanoparticle-encapsulated messenger RNA (mRNA-LNP) vaccine. Preparation of modified A-910823 adjuvants to identify which components of A-910823 play a role in driving the adjuvant effect and detailed evaluation of the immunological characteristics induced by each adjuvant showed that the induction of humoral immunity and Tfh and GCB cell induction in A-910823 were dependent on α-tocopherol. Finally, we revealed that the recruitment of inflammatory cells to the draining lymph nodes, and induction of serum cytokines and chemokines by A-910823, were also dependent on the α-tocopherol component. Conclusions: This study demonstrates that the novel adjuvant A-910823 is capable of robust Tfh cell induction and humoral immune responses, even when given as a booster dose. The findings also emphasize that α-tocopherol drives the potent Tfh-inducing adjuvant function of A-910823. Overall, our data provide key information that may inform the future production of improved adjuvants.